Poor Outcome in an Elderly Patient with Generalized Tetanus During Hospitalization: Identifying Contributing Factors - A Case Report - Iqbal Adi Prakoso; Anita Septiana Maria Kathrine; Muhammad Satri Delta Wijaya (Al Makki Publisher, 2025)
Tetanus, caused by Clostridium tetani, remains a significant global health challenge despite the availability of vaccines. This case report discusses a 64-year-old male farmer diagnosed with Grade IV generalized tetanus following a puncture wound caused by a fish bone. The patient presented with stiffness, trismus, risus sardonicus, and opisthotonus, with symptoms progressively worsening. The diagnosis was established using Ablett's classification, and treatment included tetanus antitoxin, antibiotics, diazepam, and nutritional support. However, limited healthcare resources, inadequate isolation facilities, and a lack of essential medications contributed to a poor prognosis, culminating in the patient's death. This case emphasizes the critical need for improved healthcare infrastructure, early diagnosis, comprehensive management, and public health initiatives to prevent tetanus through vaccination and education. The findings highlight the importance of addressing systemic healthcare barriers to enhance outcomes in severe tetanus cases.